Genome sequences and population genomics reveal climatic adaptation and genomic divergence between two closely related sweetgum species - Xu, Wu-Qin; Ren, Chao-Qian; Zhang, Xin-Yi; Comes, Hans-Peter; Liu, Xin-Hong; Li, Yin-Gang; Kettle, Christopher J.; Jalonen, Riina; Gaisberger, Hannes; Ma, Ya-Zhen; Qiu, Ying-Xiong (Wiley, 2024)
Understanding the genetic basis of population divergence and adaptation is an important goal in population genetics and evolutionary biology. However, the relative roles of demographic history, gene ﬂow, and/or selective regime in driving genomic divergence, climatic adaptation, and speciation in non-model tree species are not yet fully understood. To address this issue, we generated whole-genome resequencing data of Liquidambar formosana and L. acalycina, which are broadly sympatric but altitudinally segregated in theTertiary relict forests of subtropical China. We integrated genomic and environmental data to investigate the demographic history, genomic divergence, and climatic adaptation of these two sister species. We inferred a scenario of allopatric species divergence during the late Miocene, followed by secondary contact during the Holocene. We identiﬁed multiple genomic islands of elevated divergence that mainly evolved through divergence hitchhiking and recombination rate variation, likely fostered by long-term refugial isolation and recent differential introgression in low-recombination genomic regions. We also found some candidate genes with divergent selection signatures potentially involved in climatic adaptation and reproductive isolation. Our results contribute to a better understanding of how late Tertiary/Quaternary climatic change inﬂuenced speciation, genomic divergence, climatic adaptation, and introgressive hybridization in East Asia’s Tertiary relict ﬂora. In addition, they should facilitate future evolutionary, conservation genomics, and molecular breeding studies in Liquidambar, a genus of important medicinal and ornamental values.